PENGARUH PROMOSI JABATAN DAN HUBUNGAN INTERPERSONAL TERHADAP KEPUASAN KERJA PEGAWAI PT. KERETA API INDONESIA (PERSERO) DIVRE II SUMATERA BARAT - Yuliastuti, Dika; Utami, SE, MBA, Hayu Yolanda; SE, M.Si, Arnaldi, (Pendidikan Ekonomi, 2014)
ABSTRACTDika Yuliastuti, 2009 / 09090127: "Influence of Interpersonal Relations Campaign Against the Occupation and Job Satisfaction Employee PT. Kereta Api Indonesia (Persero) Division II West Sumatra". Main Supervisor : Yolanda Hayu Utami, SE, MBA Secon Supervisor : Arnaldi, SE, M.Si.This study aims to analyze: 1) The extent to which the effect of promotions on job satisfaction of employees of PT. Kereta Api Indonesia (Persero) Division II West Sumatra. 2) The extent to which the influence of interpersonal relationships on the job satisfaction of employees of PT. Kereta Api Indonesia (Persero) Division II West Sumatra. 3) The extent to which the effect of promotion and interpersonal relationships on the job satisfaction of employees of PT. Kereta Api Indonesia (Persero) Division II West Sumatra.This type of research is descriptive associative. This research was carried out for 1 month. The population of this study were all employees at PT. Kereta Api Indonesia (Persero) Division II West Sumatra totaling 87 people. The sampling technique of this study is total sampling technique that means the whole population sampled, because its population is less than 100 respondents, the sample size was 87 employees. This type of data is the primary data (ie, questionnaires) and secondary data. Data analysis was descriptive and inferential analysis through hypothesis testing using the F test and t test with α = 0.05. The results of this study menunjuikkan that: 1) a significant difference between Interpersonal Relations Campaign Against Occupation in PT. Kereta Api Indonesia (Persero) Division II West Sumatra, significance of 0.000, 2) a significant difference between Interpersonal Relations Against Employee Satisfaction in PT. Kereta Api Indonesia (Persero) Division II West Sumatra, significance of 0,000, 3) Promotion of Employment and Relations Intepersonal significant effect simultaneously on Job Satisfaction in PT. Kereta Api Indonesia (Persero) Division II West Sumatra, significance of 0.000.In this study the authors suggested that among employees further enhance interpersonal relationships with employees, namely mutual respect among fellow employee or supervisor and filled with a sense of responsibility towards the mandated employment and occupation, so that the boss can give promotions to employees in a fair, trust is based on the formation and procedures in accordance with the relevant agencies. In cooperation should be compact and harmonious team. As such conditions as it will directly impact both for employee satisfaction in PT. Kereta Api Indonesia (Persero) Division II West Sumatra, so as to achieve the goals and objectives as desired or expected by the agency.